Dimensi Sosial Disabilitas Mental di Komunitas Semin, Yogyakarta. Sebuah Pendekatan Representasi Sosial - Prakosa, Petra W. B. (Jurnal Psikologi, 2005)
The aim of this study  is to analyze the social dimension  of mental  disability  in  Semin Yogyakarta. Representational Theory as  the basic thinking of qualitative approach in this research, is used to explore the public attitude about mental disability. 20 subjects who participated were derived from 3 different groups in the society. They are 1) the professionals, 2) normal people 3) person with mental disability. The result shows that the people’s social representation about mental disability create attitude which  implies  social  interaction’s unbalancing. Each group which comes from different  social   segment  give  different representation and meaning about abnormality. It  becomes  an  individual  reference  to  act differently  in  their  community.  This  can influence the  implementation of social disability program run by professionals, and also creates a social reality for the person with mental disability and  his  family.   The  conclusion  is,   the understanding about social representational dynamic can be the strategy  in recognizing back the psychological needs of community related to mental disability problems. Keywords: representational theory, mental disability